Biological and physiological effects of pyriproxyfen insecticide and amino acid glycine on silkworm, Bombyx mori L - Saad, Mahmoud S. I. (2021)
The present investigation was carried during the spring (season 2018) to evaluate the effect of growth regulator pyriproxyfen at concentrations 1, 10, and 100 μg/larva on Bombyx mori L., as well as the effect of amino acid glycine 1% concentration solely or in combination with pyriproxyfen at the fifth day of fifth larval instar. Feeding fifth instar larvae of B. mori on mulberry leaves dipped in glycine 1% resulted in a significant increase in the weight of mature larvae and shorter larval duration, recording 5.12 g and 9.00 days, respectively. Meanwhile, the highest significant pupal weight (1.277 g) was attained when larvae were treated topically with pyriproxyfen at 10 μg/larva in the fifth day in combined with glycine 1%. Regarding technological parameters, larvae which were topically treated with pyriproxyfen at 10 μg/larva at fifth day and fed on mulberry leaves immersed in 1% glycine possessed the highest means of cocoon weight, cocoon shell weight, cocoon shell ratio, silk filament weight, and size over other treatments. The total protein and ALT were attained a higher mean recording 78.433 mg/ml and 51.053 mg/ml for control larvae, successively. Meanwhile, it showed the lowest values for total carbohydrate and AST.